2014
DOI: 10.1088/0034-4885/77/11/116503
|View full text |Cite
|
Sign up to set email alerts
|

A review of finite size effects in quasi-zero dimensional superconductors

Abstract: Quantum confinement and surface effects (SEs) dramatically modify most solid state phenomena as one approaches the nanometer scale, and superconductivity is no exception. Though we may expect significant modifications from bulk superconducting properties when the system dimensions become smaller than the characteristic length scales for bulk superconductors-such as the coherence length or the penetration depth-it is now established that there is a third length scale which ultimately determines the critical siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
80
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 188 publications
(425 reference statements)
3
80
0
Order By: Relevance
“…auto-correlation (Δ,Δ) grains 37,38 . Thus, upon increasing disorder, a transition occurs to non-superconducting state when ÎŽ loc T c .…”
Section: B Disordered Homogeneous Superconducting Filmsmentioning
confidence: 99%
“…auto-correlation (Δ,Δ) grains 37,38 . Thus, upon increasing disorder, a transition occurs to non-superconducting state when ÎŽ loc T c .…”
Section: B Disordered Homogeneous Superconducting Filmsmentioning
confidence: 99%
“…Other competing mechanisms have also been invoked to understand superconductivity in such 3D systems above the percolation threshold. Mechanisms like quantum size effects (QSE) arising in the nanoparticles and superconducting proximity effect (SPE) arising from the close proximity of the superconductor and normal metal is also expected to affect superconductivity 15 – 17 and both are known to decrease T c . In some studies, localization was also reported to affect T c in the films 18 .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, nanostructuring superconductors leads to dramatic changes in their properties compared to their bulk counterparts. These changes appear mostly once the size of the superconductor becomes smaller than the coherence length Ο 0 resulting in a modification of the critical temperature T c [4] the critical magnetic field H c [5,6] and the superconducting gap ∆ 0 [7]. Particularly, the behavior of T c has received a lot of interest since its modification depends on how nanostructuring affects the electron-phonon interaction (e-ph), reflected in the value of the electron-phonon coupling constant λ e−ph [8].…”
Section: Introductionmentioning
confidence: 99%